The Effect of Istighfar and Dhikr on Stress Reduction in Women: A Psychoreligious Approach Based on the Prophet’s Hadith - Fadhilah Is; Wasiyem; Zata Ismah; Manal Mohey Eddien Sharief (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2025)
This research is motivated by the increasing prevalence of stress in women influenced by domestic, social, and professional pressures. At the same time, psychoreligious approaches based on hadith-derived worship practices remain underexplored in scientific research. This study aims to analyze the effect of istighfar and dhikr on stress reduction in women through a psychoreligious approach, integrating the study of the Prophet’s hadith. The research method employed is a mixed-methods approach, combining quantitative surveys and qualitative analysis, involving 28 teachers, 56 students, 50 mothers, and 50 wives who participated in religious activities at the Fadhilah Quran Foundation. The results showed that the practice of istighfar and dhikr contributed significantly to stress reduction through mechanisms of releasing psychological burdens, improving emotional regulation, and strengthening spiritual awareness, thereby impacting affective stability. Quantitative analysis confirmed a decrease in mean stress before and after the practice with a strong level of significance. At the same time, qualitative data revealed the formation of consistent subjective experiences of calm, focus, and positive reinterpretation of life’s pressures. These findings confirm that integrating istighfar and dhikr can serve as an effective psychoreligious intervention model for women’s empowerment and provide theoretical contributions to the development of Islamic psychology and hadith studies.